STUDIES ON PHOSPHOLIPASE C FROM MELIA AZADIRACHTA SEEDS (Journal of Sciences, Islamic Republic of Iran)
The activity of phospholipase C in crude enzymatic preparation of Melia azadiracht seeds (Neem seeds) was studied by the use of lecithin as a substrate in aqueous medium. The enzyme activity was found optimum at pH 2.5 and temperature 35?C. The phospholipase C was found heat labile, being inactivated 88% within 10 minutes at 90°C